-6z+-16z-(-7z)=15

Simple and best practice solution for -6z+-16z-(-7z)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6z+-16z-(-7z)=15 equation:



-6z+-16z-(-7z)=15
We move all terms to the left:
-6z+-16z-(-7z)-(15)=0
determiningTheFunctionDomain -6z-16z-(-7z)-15+=0
We add all the numbers together, and all the variables
-22z-(-7z)=0
We get rid of parentheses
-22z+7z=0
We add all the numbers together, and all the variables
-15z=0
z=0/-15
z=0

See similar equations:

| 1/2h-5=1 | | 4=6+x/2 | | (30-2x)+(24-2x)=(4*x)4 | | x+7(4)=( | | -3x+52+x+21=2 | | 5p(-3)=252 | | (1/3)^4x=9 | | 5x-(x-2)=2x-4(x-8) | | 4x+2=8x-9 | | 54-4x=4x*4 | | P(x)=8x-10 | | 6x+4=9x+4 | | 5x+4=-x-5 | | 7n+6=3n | | −6y−11y-17=−82 | | x+7(0)=9 | | 3(4a-3)=15 | | m4– 2= 2 | | 3(1/4-x/5)/2=5(x-3/4)-4(x-3/4) | | 4x^2-3=1-X | | 2−.20r=2r+1 | | 18=-7y+5(y+4) | | 8(x+7)=2+8x | | 4+2b=5+5(b+4) | | 3=-3x=33 | | x+7(-1)=9 | | 3x+20=135 | | m/4+9=12 | | 15p-(-4p)=19 | | -1/9+z=8/9 | | (6x-2)+92=180 | | -6x+1=-x-3 |

Equations solver categories